PENGATURAN HUKUM PERETASAN SITUS WEBSITE YANG DILAKUKAN OLEH WNA DITINJAU DARI UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Putera Semadi, Anak Agung Gde; Manika, Agus Surya; Harisandhi, I Gede Manik (Kerta Dyatmika, 2024)
Law Number 19 of 2016 concerning Information and Electronic Transactions in Article 1 number 21 that what is meant by Persons are individuals, both Indonesian citizens, foreign citizens, and legal entities, so that these rules can ensnare perpetrators who are foreign citizens.The purpose of this study is to determine the regulations for hacking websites according to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions and the legal consequences for a website hacker who is a foreign citizen.The research method used is a normative research method that relies on the approach of concepts and norms and laws with data collection techniques through literature study. Arrangements for hacking websites according to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions are regulated in Article 30 paragraphs 1, 2 and 3 of Law Number 19 of 2016 concerning Amendments to Laws -Law Number 11 of 2008 Concerning Information and Electronic Transactions Temporary Legal consequences for a website hacker who is a foreign citizen may be subject to sanctions based on Article 46 of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions.